Analysis of the threshold stress in the Al-Ti alloys exhibiting high strain rate superplasticity - Kum, D. (Trans Tech Publications Ltd, 1997)
Gas atomized powders of Al-10wt%Ti alloy has been consolidated by powder metallurgy(P/M) involving hot extrusion, and fine microstructure consists of equiaxed grain and flake-shape Al3Ti was produced. High strain rate superplasticity(HSRS) has been investigated at 600-650°C and strain rate of 10-3-10° sec-1 in tension, and total elongation of 300 - 500% was observed at strain-rate of 10-1 sec-1. The HSRS deformation has been illustrated by incorporating threshold stress, which decreases apparent flow stress, and interpreted as grain boundary sliding accomodated by dislocation slip inside grains based on analyses of strain-rate sensitivity, activation energy for deformation and transmission electron microscopy after superplastic deformation. The determined threshold stress showed strong temperature dependency as in the case of steady state creep of other P/M Al-Ti alloys. It has been anlyzed by thermally activated process, and the activation energy for the threshold stress is determined to be 149.1±24.3kJ/mole at the superplastic condition. A model based on dislocation interaction with solute atoms during the accomodation process is suggested as the source of the threshold stress. The unusually high activation energy for HSRS deformation at very high temperatures is explained by the proposed model.